Carbohydrate Content in Packaged Chicken Nuggets: Qualitative And Quantitative Analysis - Syifa Alifia Indriani; Nurul Asfia; Agnes Manongga; Riong Seulina Panjaitan (Department of Pharmacy, Muhammmadiyah University of Sumatera Barat, 2022)
Nugget products can be made from beef, chicken, fish, and other ingredients, but chicken nuggets are the most popular in the community. Chicken nuggets are products produced from the marinated, ground, minced, and cooked parts of chicken breast meat with breadcrumbs. Qualitative and quantitative tests of carbohydrates are carried out to determine the presence of carbohydrates present in nuggets. Qualitative tests are based on changes in color or deposits formed, while quantitative tests to determine the carbohydrate levels contained in each test material with DNS method. The results showed qualitative analysis of molisch test carbohydrates on samples of chicken meat nuggets brand